2021
DOI: 10.1038/s41467-021-24843-w
|View full text |Cite
|
Sign up to set email alerts
|

Super enhancer regulation of cytokine-induced chemokine production in alcoholic hepatitis

Abstract: Alcoholic hepatitis (AH) is associated with liver neutrophil infiltration through activated cytokine pathways leading to elevated chemokine expression. Super-enhancers are expansive regulatory elements driving augmented gene expression. Here, we explore the mechanistic role of super-enhancers linking cytokine TNFα with chemokine amplification in AH. RNA-seq and histone modification ChIP-seq of human liver explants show upregulation of multiple CXCL chemokines in AH. Liver sinusoidal endothelial cells (LSEC) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 67 publications
0
73
0
1
Order By: Relevance
“…[120] Our group and others demonstrated activation of cytokine pathways and chemokine production in AH. [121,122] Our initial transcriptomic study showed remarkable changes in the transcriptome and epigenome of AH cirrhotic livers, which were also accompanied by the upregulation of several CXCL chemokines. By using 3C, 4C, and analysis…”
Section: D Epigenomics and Arldmentioning
confidence: 99%
See 1 more Smart Citation
“…[120] Our group and others demonstrated activation of cytokine pathways and chemokine production in AH. [121,122] Our initial transcriptomic study showed remarkable changes in the transcriptome and epigenome of AH cirrhotic livers, which were also accompanied by the upregulation of several CXCL chemokines. By using 3C, 4C, and analysis…”
Section: D Epigenomics and Arldmentioning
confidence: 99%
“…[148] The regulation and function of chemokines in liver disease was reviewed thoroughly by Cao et al [148] As described previously, our group described the role of super-enhancers in regulating inflammation in ARLD, particularly upregulation of several CXCL chemokines. [121] The bromodomain and extraterminal (BET) family comprises epigenetic reader proteins. BET proteins are known to bind with super-enhancers and modulate super-enhancers function in inflammatory conditions.…”
Section: Drugs Targeting Epigenetic Regulation and Arldsmentioning
confidence: 99%
“…liver inflammation [8]. Indeed, TNF-α binds its cognate receptor at the surface of liver sinusoidal endothelial cells (LSECs) to activate nuclear factor κB family, regulate a super enhancer, and induce multiple C-X-C motif chemokines (in particular, growthregulated alpha protein [encoded by CXCL1], interleukin (IL)-8 [encoded by CXCL8]) [18]. These LSEC-produced chemokines attract and activate circulating neutrophils which then infiltrate the liver where they release ROS [8,19].…”
Section: Inducers Of Alcoholic Hepatitismentioning
confidence: 99%
“…However, few studies focus on the role of SIRT in ALD, which should be especially studied in the future. Additionally, inhibition of histone acetylation reader BRD4 either by epigenome editing or selective inhibitor iBET-151 could suppress the chemokine expression in liver sinusoidal endothelial cells (LSECs) and reduce neutrophil infiltration in murine models of alcoholic hepatitis ( Figure 2 ) ( Liu et al, 2021 ). These results imply that histone acetylation are indeed involved in the inflammatory response of alcoholic hepatitis, and that the role of histone acetylation depends to some extent on the involvement of readers.…”
Section: Histone Modifications In Cldsmentioning
confidence: 99%
“…Interestingly, SIRT1 is downregulated during organ injury and aging-associated fibrosis ( Han et al, 2021 ), which means SIRT1 can also be a new therapeutic target in liver fibrosis. Chromatin reader BRD4 is the reader of H3K27ac, and the BRD4 inhibitor iBET-151 could ameliorate hepatic inflammation and liver injuries in CCl 4 -induced acute liver injury and alcoholic hepatitis ( Gao et al, 2021 ; Liu et al, 2021 ). Therefore, the histone acetylation readers could also be a potential target for the treatment of CLD.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%